GENDER-BASED DEBATES IN POPULAR DOLL SONGS - Sobati, Chandrappa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Doll art is a man's art. Only men should play the doll instrument. Why is that? Only men should touch this instrument. Traditional beliefs and taboos that require participation in this art form were once alive here. Today, none of the concepts and taboos mentioned above apply to doll art. This is a healthy development. Because, women have come to this field of art and have gained as much proficiency and popularity as men in the specialty of performance. This art is being performed in other contexts besides traditional performances. It is in the context of political campaigning, entertainment, and different occasions of earning money, etc. While this change has brought some healthy development here, it has also brought some unhealthy development. Today, it would not be an exaggeration to say that women outnumber men in singing doll songs. Some other women have taken the initiative to revive this art form in different settings. Some of them have succeeded. This is also a promising development. Amidst many such developments, there are things like 'acceptance' and 'denial' among men about the arrival of these women. This trend is also happening intensively in song performances. There are more denials in this. This trend has led to various arguments. Although there are many reasons for this, senior artists believe that the main reason is the nature of the performance. This is somewhat correct. But this is not the complete reason either. That is, women's performances are not being performed in the shadow of religion or within the framework of the traditional cultural identity of the Halut. They are not performing their expressions in the religious field of the Halut religion and are only performing art on popular platforms. Due to this, they are only seen as expressions of capitalist songs. Therefore, there are arguments that she has been formed or portrayed in this field and among the audience only as an artist who performs for capital and personal prestige. It is not possible to accept this argument universally. This is due to the tradition of this field of art.